The Effect Of Connectivity On Smart Safety Light Sign - Muhammad Nurhuda H; Wakhid Wijaya; Uyock Anggoro Saputro (SISFOTENIKA, 2022)
The higher the community's mobility and the more road users, the more the risk of accidents on the road will increase. Indonesia itself is ranked 5th in the world with the highest accident rate. Many factors influence the occurrence of accidents, not only from humans but also from nature. It could also be due to limited road information for motorists in traffic signs. As a driver's information medium, signs should have a strategic point and be easy to see for motorists. One way to do this could be to modernize signs by utilizing newer technologies such as sensors and LEDs. This study proposes a prototype of a traffic sign using sensors, LEDs, and an Arduino microcontroller. The proposed sign is a bend indicator LED light attached to sharp turns and automatically lights up as the vehicle passes around the sign sensor. The sensor used is an ultrasonic sensor HC-SR04 which has a response distance of up to 4 meters. The research focuses on the media connection between devices with wired and wireless media. This study will test the results of sensor accuracy values with wired and wireless connectivity.